Nueva localidad para Avellanita bustillosii Phil. (Euphorbiaceae) en la Región de O´Higgins y su estado de conservación - MEDINA, PATRICIO; ROJAS, GLORIA (Gayana Botánica, 2018)
A new record for Avellanita bustillosii Phil. is added. Botanical surveys in pre-andean mountain range of O´Higgins Region leads to find a new population. Their distributional southern limit is extended about 26.5 km. This population was found between 700 and 880 masl, in the northern slope of the Retamal foothill and the slopes with eastern exposure of the Trocalán hill, both located at 11 km east of the town of Requinoa, Cachapoal Province, O´Higgins Region. This finding it´s a contribution to the taxon chorology and reveals the lack of information available about their distributional territory. This is the first population described to Central Chile pre-andean mountain range. A re-evaluation to its conservation status is provided.